Leaving No One Behind in Access to Higher Education in the Baltic States and Poland - Pikturnaitė, Ilvija; Paužuolienė, Jurgita; Mironova, Julija; Karczewska, Małgorzata (Ital Publication, 2025)
The article presents research on the accessibility of higher education in the Baltic States and Poland and its compliance with the principle of “Leaving No One Behind”. A qualitative approach was used to achieve the research objective using analysis of statistical indicators and the contents of documents. The results of the study reveal that the progress on higher education attainment is not homogeneous and not consistent in the countries analyzed. Document analysis indicates that higher education accessibility differs across Lithuania, Latvia, Estonia, and Poland. Lithuania and Latvia are the most accessible due to unified application systems, while Poland lacks such a system, creating extra costs and delays. A comparison of the mandatory examinations and minimum requirements set by the countries shows that Lithuania has the highest barriers to access to higher education: people with lower results or learning gaps in secondary education are deprived of the opportunity to acquire higher education, and their chances of avoiding falling behind are lower. Lithuania does not provide for exceptions for the admission of people with disabilities: they must meet the same requirements as other applicants. Another group of people who may face exclusion in Lithuania, Latvia, and Poland are members of national minorities. These results suggest that the governments of the countries and universities need to be more inclusive in their admission policies.